1959
DOI: 10.1126/science.129.3364.1672
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Adaptive Control of Levels of Rat Liver Tryptophan Transaminase

Abstract: The dual control by substrate and hormone of the level of a third adaptive enzyme in animals is described. Injections of hydrocortisone or the substrate tryptophan increased the level of the liver tryptophan-alpha-ketoglutarate transaminase of intact rats within 5 hours. In adrenalectomized rats this enzyme level was increased by hydrocortisone alone, but substrate induction could be demonstrated only if these animals were treated at the same time with hydrocortisone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1962
1962
1980
1980

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…14C from L-[carboxy-"4C]tryptophan may be eliminated at several stages of tryptophan metabolism: (i) as [1-14Clalanine by the action of kynureninase on L-kynurenine or 3-hydroxy-Lkynurenine (McDermott et al, 1973); (ii) as 14CO2 by decarboxylation of tryptophan to tryptamine (Weissbach et al, 1959); rapid conversion of [1-14C]alanine into [1-14Clpyruvate by high alanine aminotransferase activity in liver and the subsequent oxidative decarboxylation of pyruvate would lead to the appearance of label as 14CO2; (iii) as 14CO2 by oxidation of indol-3-ylpyruvate to indol-3-ylacetate after transamination of tryptophan with 2-oxoglutarate (Civen & Knox, 1959); (iv) as 14CO2 by decarboxylation of 5-hydroxytryptophan to 5-hydroxytryptamine after metabolism of tryptophan by tryptophan hydroxylase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14C from L-[carboxy-"4C]tryptophan may be eliminated at several stages of tryptophan metabolism: (i) as [1-14Clalanine by the action of kynureninase on L-kynurenine or 3-hydroxy-Lkynurenine (McDermott et al, 1973); (ii) as 14CO2 by decarboxylation of tryptophan to tryptamine (Weissbach et al, 1959); rapid conversion of [1-14C]alanine into [1-14Clpyruvate by high alanine aminotransferase activity in liver and the subsequent oxidative decarboxylation of pyruvate would lead to the appearance of label as 14CO2; (iii) as 14CO2 by oxidation of indol-3-ylpyruvate to indol-3-ylacetate after transamination of tryptophan with 2-oxoglutarate (Civen & Knox, 1959); (iv) as 14CO2 by decarboxylation of 5-hydroxytryptophan to 5-hydroxytryptamine after metabolism of tryptophan by tryptophan hydroxylase.…”
Section: Resultsmentioning
confidence: 99%
“…Studies with cell-free extracts have shown that, in addition to enzymes required for the kynurenine pathway, the liver possesses the necessary enzymic complement for the catabolism of tryptophan by each of the other three pathways (Weissbach et al, 1959;Civen & Knox, 1959;Renson et al, 1966 Cell incubation conditions and assay procedures (i) Measurement of radioisotope release from radioisomers of L-tryptophan. The incubation conditions for determining rates of 14CO2 production from "4C-labelled tryptophan radioisomers were identical with those described previously (Smith & Pogson, 1980).…”
mentioning
confidence: 99%
“…This conclusion rests on studies employing drug dosage levels in the pharmacologic range and drug action period considerably longer than necessary to show a marked response to an inciting stimulus (4,6,8,13). For instance, either the intraperitoneal or intravenous injection of iV of the L-tryptophan standard dose produced a marked increase in hepatic TP activity in intact rats within 1 hour; in dogs a somewhat greater response was obtained with -£$ of this dose (2).…”
Section: Discussionmentioning
confidence: 92%
“…In view of the rapidity and sensitiveness of the mechanisms operative in these cases, and of the reduced response following adrenalectomy (Table 1), it would seem to be of rather limited usefulness to regard the function of the adrenal steroids in the intact organism solely from the standpoint of their inducing action. Furthermore, it is difficult to extract from the previously cited studies an insight into the function of the adrenal secretory product in the presence of increased plasma levels of the specific substrate (13).…”
Section: Discussionmentioning
confidence: 99%
“…A high level of dietary vitamin E might result in lowering the concentration of lipid peroxides in the tissues, thereby sparing the need for GSH peroxidase, the decomposer of lipid peroxides. Substrate induction is known to be an important factor for the synthesis of certain enzymes (18); for example, the activity of tryptophan pyrrolase in liver has been shown to increase in rats in response to the administration of its substrate, tryptophan (19,20). It has been shown (1 5 , 21, 22) that the accumulation of fluoresent products (believed to be products of lipid peroxidation) in tissues is related to the level of dietary vitamin E. The reduced oxidative stress might be part of the reason for lower activity of GSH peroxidase in tissues of rats given high levels of vitamin E.…”
Section: Discussion Many Factors Such As Dietary Levels Of Seleniummentioning
confidence: 99%